World vision Burundi adopts AID-I GLR approach for its projects - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
World Vision International (WVI) leads a consortium of partners implementing AID-GLR scaling efforts in Burundi, working mainly on several value chains: beans, livestock, maize, orange-fleshed sweet potatoes and rice. But it doesn't stop there. WVI is further applying the AID-I GLR method for a World Food Programme (WFP) project on household resilience – reaffirming that our methods work. For efficient delivery of technology, aspects transferred from AID-I GLR to the WFP project include demonstration plots, small packs, village-based advisors, collaborations and connections, and training. Hear all about it from Fiacre Nkeshimana, Grant Manager, WVI Burundi.